NORMAL REFERENCE HEMATOLOGICAL VALUES OF ONE-HUMPED CAMELS (CAMELUS DROMEDARIUS) KEPT IN CHOLISTAN DESERT - U. Farooq; H. A. Samad; A. Khurshid; S. Sajjad (Journal of Animal and Plant Sciences, 2011)
Reference normal hematological values have been documented for various domestic animals under various climatic/geographical conditions; however there is a dearth of information in the literature concerning these values for camels kept in desert. The present pilot study was conducted to establish reference normal range of salient hematological parameters in clinically healthy camels (30 males and 30 females) being reared in a farm of Desert Rangers, Cholistan, in order to form a basis for clinical interpretation. Blood samples were aseptically collected and were analyzed for hematological parameters. The mean values for hemoglobin (Hb), Packed Cell Volume (PCV), Total Erythrocyte Count (TEC), Total Leukocyte Count (TLC), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC) for males were 12.00±0.63 g/dl, 37.21 ±2.48 %, 6.83±0.38 x 106/μl, 12.38±0.97x 103/μl, 57.13±5.09 fl, 18.69±1.45 pg, and 33.61±1.42; and for females were 11.34±0.95 g/dl, 32.83 ±3.76 %, 7.31±0.58 x 106/μl, 12.97±0.99x 103/μl, 50.24±7.72 fl, 17.80±2.21 pg, and 34.81±2.16, respectively. The difference in values were statistically non significant for males and females. The Differential Leukocyte Count (DLC) revealed that the lymphocytes were the predominant leucocytes which are typical of most other ruminants.
Keywords: Cholistan; camel; hematology